Mimicking age-associated Gadd45γ dysregulation results in memory impairments in young adult mice - Brito, David V. C.; Kupke, Janina; Gülmez Karaca, Kübra; Zeuch, Benjamin; Oliveira, Ana (The journal of neuroscience, 2020)
Age-related memory loss is observed across multiple mammalian species and preferentially affects hippocampus-dependent memory. Memory impairments are characterized by accelerated decay of spatial memories. Nevertheless, the molecular mechanisms underlying these deficits are still largely unknown. Here, we investigated the expression and function of the growth arrest DNA damage (Gadd45) family during aging and cognition, respectively.